Improved photon absorption in dye-functionalized silicon nanocrystals synthesized via microwave-assisted hydrosilylation. Issue 7 (4th February 2020) - Beri, Deski; Jakoby, Marius; Howard, Ian A.; Busko, Dmitry; Richards, Bryce S.; Turshatov, Andrey
Abstract : Silicon nanocrystals with dyes covalently anchored to the crystal surface demonstrate improved visible light absorption and near-infrared luminescence enhancement – up to ∼270% and ∼140% under excitation with blue and green light, respectively. Abstract : Herein, we report a method to produce luminescent silicon nanocrystals (SiNc) that strongly absorb ultraviolet–visible light (300–550 nm) and emit in the near-infrared range (700–1000 nm) with a high photoluminescence quantum yield (PLQY). Using microwave-assisted hydrosilylation and employing reactive chromophores – such as ethenyl perylene, ethynyl perylene and ethylene- m -phenyl BODIPY – we are able to achieve a 10- and 3-fold enhancement of the absorption in the blue and green spectral range, respectively. The investigated dyes function both as passivating agents and highly efficient antenna, which absorb visible light and transfer the energy to SiNc with an efficiency of >95%. This enhanced absorption leads to a significant photoluminescence enhancement, up to ∼270% and ∼140% under excitation with blue and green light, respectively. Despite the gain in absolute brightness of the emission, we demonstrate that back energy transfer from the SiNc to the dyes leads to a decrease in the PLQY for dye-modified SiNc, as compared to unmodified SiNc. The synthesis of the SiNc-dye conjugates opens up new possibilities for applications of this abundant and non-toxic material in the field of solar energy harvesting, optical sensing and bioimaging via achieving strong NIR PL excited with visible light.